What is constituted as mathematics when presented in contextually embedded forms? : a study based on two activities from the 2003 Grade 9 Common Task for Assessment for Mathematics - Ebrahim, Rushdien (School of Education, 2014)
This study focuses on what comes to be constituted as mathematics when is presented in contextually embedded forms, how students constitute mathematical meaning from such texts, and what is constituted as mathematics when this particular form of mathematics is pedagogised.